Extracellular Traps Increase Burden of Bleeding by Damaging Endothelial Cell in Acute Promyelocytic Leukaemia - Wang, Yufeng; Wang, Chunxu; Zuo, Nan; Yang, Hao; Fang, Shaohong; Shi, Jialan (Frontiers in Immunology, 2022)
The rate of complete remission of acute promyelocytic leukemia (APL) is currently over 90% because of the use of all-trans retinoic acid (ATRA) with arsenic trioxide (ATO). However, hemorrhagic mortality has emerged as the most significant barrier to APL-induced remission. Neutrophils extracellular traps (NETs/ETs) cause vascular leakage by damaging the integrity of endothelial cells. We have previously demonstrated that APL cells treated with ATRA/ATO undergo a cell death process, releasing extracellular chromatin, termed ETosis/NETosis. However, the mechanism underlying the involvement of ETs in endothelial injury in APL remain largely unknown. Here, we analysed the ability of mature and immature neutrophils to release ETs, and their interaction with platelets (PLTs) in APL. Importantly, the effect of ETs on vascular endothelium in APL was discussed. Our results showed that the ability of immature neutrophils to release ETs was impaired in APL, whereas mature neutrophils produced ETs, which were associated with activated PLTs. Moreover, ATRA+ATO induced immature neutrophil differentiation, as well as increased the release of ETs from mature neutrophils. The excessive ETs damaged endothelial cells, causing blood cell leakage. Removing ETs using DNase 1 alleviated endothelial damage and improved blood cells leakage. Our results indicate that vascular endothelial injury is at least partially associated with ETs in APL, and that targeting ETs production may be an effective approach for relieving vascular leakage and reducing the burden of bleeding in APL.